The Ntui-Betamba high-Grade gneisses: a northward extension of the Pan-African Yaounde gneisses in Cameroon - Nono Djoum Franka (Jurnal Ilmiah MTG, 2010)
The Ntui-betamba area (southern Cameroon) is composed of high-grade migmatitic gneisses in which two litholigical units are distinguished: (i) a metasedimetary unit (kyanite-biotite-garnet gneisses, biotite-muscovite-garnet gneisses, calc-silicate rocks and quartzites) interpreted as a continental margin sedimentary series; and (ii) meta-igneous rocks comprising alkaline ultramafic to mafic pyroxene gneisses and amphibolites and amphibole-bearing alkaline orthogneisses. These units recrystallised under HP-HT conditions (T= 750-800°C, P≥ 0.9-1.3 GPa) and were deformed in relation to major tangential tectonic event with north-northeast-south-southwest kinematic direction. This lithological association its tectono-metamorphic evolution show striking similarities with the Yaounde gneisses, suggesting that the extensional depositional environment envisaged for this formation can be extended farther north, towards the Adamawa Shear Zone (Lom Series). The contrasted metamorphic evolution between areas located to the south of the (high pressure: Yaounde, Ntui-Betamba), and those located to the north (low pressure: Banyo), along with widespread remains of a palæoproterozoic crust, suggest important crustal thickening during tangential tectonics in southern Cameroon. As a consequence, the Adamawa Shear Zone is not simply a late Pan-African transcurrent transpressive Shear Zone but appears to have been formerly a major (possibly intracontinental) thrust zone.